Pattern Recognition Receptor-reactivity Screening of Liver Transplant Patients: Potential for Personalized and Precise Organ Matching to Reduce Risks of Ischemia-reperfusion Injury. Issue 5 (May 2020) - Sosa, Rebecca A.; Rossetti, Maura; Naini, Bita V.; Groysberg, Victoria M.; Kaldas, Fady M.; Busuttil, Ronald W.; Chang, Yu-Ling; Gjertson, David W.; Kupiec-Weglinski, Jerzy W.; Reed, Elaine F.
Abstract : Objective and Background: Pattern recognition receptors (PRRs) on immune and parenchymal cells can detect danger-associated molecular patterns (DAMPs) released from cells damaged during ischemia-reperfusion injury (IRI), in heart attack or stroke settings, but also as an unavoidable consequence of solid organ transplantation. Despite IRI being a significant clinical problem across all solid organ transplants, there are limited therapeutics and patient-specific diagnostics currently available. Methods: We screened portal blood samples obtained from 67 human liver transplant recipients both pre- [portal vein (PV) sample] and post-(liver flush; LF) reperfusion for their ability to activate a panel of PRRs, and analyzed this reactivity in relation to biopsy-proven IRI. Results: PV samples from IRI+ orthotopic liver transplantation (OLT) patients (n = 35) decreased activation of hTLR4- and hTLR9-transfected cells, whereas PV from IRI− patients (n = 32) primarily increased hTLR7 and hNOD2 activation. LF samples from OLT-IRI patients significantly increased activation of hTLR4 and hTLR9 over IRI− LF. In addition, the change from baseline reactivity to hTLR4/9/NOD2 was significantly higher in IRI+ than IRI− OLT patients. Conclusions: These results demonstrate that TLR4/7/9 and NOD2 are involved in either promoting or attenuating hepatic IRI, and suggest a diagnostic screening of portal blood for reactivity to these PRRs might prove useful for prediction and/or therapeutic intervention in OLT patients before transplantation. Abstract : Supplemental Digital Content is available in the text